Rapid Identification of Emerging Human-Pathogenic Sporothrix Species with Rolling Circle Amplification - Rodrigues, Anderson M.; Najafzadeh, Mohammad J.; de Hoog, G. Sybren; de Camargo, Zoilo P. (Frontiers in Microbiology, 2015)
Sporothrix infections are emerging as an important human and animal threat among otherwise healthy patients, especially in Brazil and China. Correct identification of sporotrichosis agents is beneficial for epidemiological surveillance, enabling implementation of adequate public-health policies and guiding antifungal therapy. In areas of limited resources where sporotrichosis is endemic, high-throughput detection methods that are specific and sensitive are preferred over phenotypic methods that usually result in misidentification of closely related Sporothrix species. We sought to establish rolling circle amplification (RCA) as a low-cost screening tool for species-specific identification of human-pathogenic Sporothrix. We developed six species-specific padlock probes targeting polymorphisms in the gene encoding calmodulin. BLAST-searches revealed candidate probes that were conserved intraspecifically; no significant homology with sequences from humans, mice, plants or microorganisms outside members of Sporothrix were found. The accuracy of our RCA-based assay was demonstrated through the specificity of probe-template binding to 25 S. brasiliensis, 58 S. schenckii, 5 S. globosa, 1 S. luriei, 4 S. mexicana, and 3 S. pallida samples. No cross reactivity between closely related species was evident in vitro, and padlock probes yielded 100% specificity and sensitivity down to 3 x 10 6 copies of the target sequence. RCA-based speciation matched identifications via phylogenetic analysis of the gene encoding calmodulin and the rDNA operon (kappa 1.0; 95% confidence interval 1.0-1.0), supporting its use as a reliable alternative to DNA sequencing. This method is a powerful tool for rapid identification and specific detection of medically relevant Sporothrix, and due to its robustness has potential for ecological studies.